Preparation method and structure of perovskite battery
By introducing an interface passivation layer between the perovskite absorbing layer and the electron transport layer of the perovskite solar cell, the passivation layer material of the piperazine carboxylic acid compound is solved, and the overall performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411667337.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The performance of perovskite solar cells is affected by grain boundary defects inside the perovskite thin film layer and interface defects between the perovskite thin film layer and the charge transport layer, resulting in a decrease in carrier life and a decrease in cell performance.
By introducing a specific interface passivation layer between the perovskite light absorbing layer and the electron transport layer, a passivation treatment solution is formed by mixing piperazine carboxylic acid compounds with organic solvents, and annealing is performed to form an interface passivation layer. The passivation layer material includes piperazine groups and carboxylic acid groups, which can form coordination bonds with metal cations on the perovskite surface, passivate grain boundary defects and reduce the density of interface defect states.
It effectively passivates defects on the surface and grain boundaries of the perovskite absorber layer, reduces the interface defect state density between the perovskite absorber layer and the electron transport layer, suppresses the non-radiative recombination process, and improves the carrier extraction efficiency and overall battery performance.
Smart Images

Figure CN119546140A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells and relates to a preparation method and structure of a perovskite cell. Background Art
[0002] Perovskite cells, as an emerging photovoltaic technology, have become a hot topic in the photovoltaic field due to their simple structure, low cost, excellent photoelectric performance and simple preparation process. Perovskite materials themselves have excellent photoelectric conversion properties, such as high absorption coefficient, long carrier diffusion length and high carrier mobility. These properties have enabled the efficiency of perovskite solar cells to rapidly surpass traditional silicon-based solar cells in just a few years.
[0003] However, the performance of perovskite solar cells has been affected by the internal grain boundary defects of the perovskite film layer and the interface defects between the perovskite film layer and the charge transport layer. These defects will lead to an increase in non-radiative recombination, thereby reducing the carrier lifetime and weakening the battery performance. In particular, the interface defects between the perovskite film layer and the charge transport layer, whose defect state density is usually 1-2 times higher than that inside the film, have a significant negative impact on the overall efficiency of the battery.
[0004] Therefore, how to provide a preparation method and structure of a perovskite battery to reduce the interface defects between the perovskite thin film layer and the charge transfer layer and passivate the grain boundary defects of the perovskite thin film layer has become an important technical problem that needs to be solved urgently by technicians in this field.
[0005] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present application and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because they are described in the background technology section of the present application. Summary of the invention
[0006] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a method and structure for preparing a perovskite cell, which is used to solve the problem in the prior art that the performance of the perovskite cell is reduced due to grain boundary defects inside the perovskite film layer and interface defects between the perovskite film layer and the charge transfer layer.
[0007] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a perovskite battery, comprising the following steps:
[0008] Providing a conductive substrate, and forming a first hole transport layer on the conductive substrate;
[0009] forming a first perovskite light absorbing layer on the first hole transport layer;
[0010] Mixing a piperazine carboxylic acid compound and an organic solvent in a preset ratio to form a passivation treatment solution, coating the passivation treatment solution on the surface of the first perovskite light absorbing layer, and performing an annealing treatment to form a first interface passivation layer;
[0011] forming a first electron transport layer on the first interface passivation layer;
[0012] A first electrode layer is formed on the first electron transport layer.
[0013] Optionally, the piperazine carboxylic acid compound includes at least one of piperazine-DL-malate, 2-piperazineacetic acid and 4-piperazinebenzoic acid.
[0014] Optionally, the concentration range of the piperazine carboxylic acid compound in the passivation treatment solution is 0.1 to 2 mg / mL.
[0015] Optionally, the thickness of the first interface passivation layer is in the range of 1 to 15 nanometers.
[0016] Optionally, the organic solvent includes at least one of isopropanol, methanol, ethanol and ethyl acetate.
[0017] Optionally, the material of the first perovskite light absorbing layer has a general structural formula of ABX3, wherein A is MA + , FA + , Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ ,Ge 2+ Any one or a combination of at least two of the following, X is F - , Cl - ,I - Br - Any one or a combination of at least two of the following.
[0018] Optionally, the method further includes forming a bottom battery structure layer, wherein the bottom battery structure layer is formed on a surface of the first electrode layer.
[0019] Optionally, the formation of the bottom battery structure layer comprises the following steps:
[0020] forming a second hole transport layer on the first electrode layer;
[0021] forming a second perovskite light absorption layer on the second hole transport layer, wherein the bandgap width of the material of the second perovskite light absorption layer is smaller than the bandgap width of the material of the first perovskite light absorption layer;
[0022] forming a second interface passivation layer on the second perovskite light absorbing layer;
[0023] forming a second electron transport layer on the second interface passivation layer;
[0024] A second electrode layer is formed on the second electron transport layer.
[0025] Optionally, the process of forming the second interface passivation layer includes: preparing a passivation solution, coating the passivation solution on the second perovskite light absorbing layer, and performing annealing to form the second interface passivation layer, wherein the composition of the passivation solution used to form the second interface passivation layer is the same as or different from the composition of the passivation treatment solution used to form the first interface passivation layer.
[0026] The present invention also provides a perovskite battery structure, which includes a conductive substrate, a first hole transport layer, a first perovskite light absorption layer, a first interface passivation layer, a first electron transport layer and a first electrode layer stacked in sequence, wherein the perovskite battery structure is obtained by any one of the above-mentioned perovskite battery preparation methods.
[0027] As described above, the present invention provides a method and structure for preparing a perovskite cell, which significantly improves the performance of the perovskite cell by introducing a specific interface passivation layer between the first perovskite light absorbing layer and the first electron transport layer. The introduction of the interface passivation layer effectively passivates the defects on the surface of the first perovskite light absorbing layer and at its grain boundaries, and reduces the interface defect state density between the first perovskite light absorbing layer and the first electron transport layer, thereby effectively suppressing the occurrence of non-radiative recombination processes. In addition, the interface passivation layer also optimizes the band structure of the first perovskite light absorbing layer, significantly improves the carrier extraction efficiency, and thus greatly improves the overall performance of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Shown is a process flow chart of the method for preparing the perovskite battery of the present invention.
[0029] Figure 2 It is a schematic diagram of the cross-sectional structure of a perovskite cell formed in Example 1 according to the method for preparing a perovskite cell of the present invention.
[0030] Figure 3 The figure shows a scanning electron microscope image of a method for preparing a perovskite cell of the present invention after forming a first interface passivation layer on the surface of the first perovskite light-absorbing layer in a specific example.
[0031] Figure 4 Shown is a current density and voltage characteristic curve of a perovskite cell formed in a specific example of the perovskite cell preparation method of the present invention.
[0032] Figure 5The scanning electron microscope image is shown when the first interface passivation layer is not formed on the surface of the first perovskite light absorbing layer in the comparative example.
[0033] Figure 6 Shown is the current density and voltage characteristic curve of the perovskite battery formed in the comparative example.
[0034] Figure 7 Shown is a box plot of the power conversion efficiency of the perovskite cells formed according to a specific example of the present invention and a comparative example.
[0035] Figure 8 It is a schematic diagram showing the cross-sectional structure of a perovskite cell formed in Example 2 according to the method for preparing a perovskite cell of the present invention.
[0036] Description of Figure Numbers
[0037] 111 Conductive substrate
[0038] 112 first hole transport layer
[0039] 113 The first perovskite light-absorbing layer
[0040] 114 First interface passivation layer
[0041] 115 First electron transport layer
[0042] 116 First buffer layer
[0043] 117 first electrode layer
[0044] 121 Second hole transport layer
[0045] 122 Second perovskite light absorbing layer
[0046] 123 Second interface passivation layer
[0047] 124 Second electron transport layer
[0048] 125 Second buffer layer
[0049] 126 second electrode layer
[0050] Steps S1 to S5 DETAILED DESCRIPTION
[0051] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0052] See also Figures 1 to 8 It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0053] Embodiment 1
[0054] The present invention provides a method for preparing a perovskite battery. Figure 1 , shown as a process flow chart of the method, comprising the following steps:
[0055] S1: providing a conductive substrate, and forming a first hole transport layer on the conductive substrate;
[0056] S2: forming a first perovskite light absorbing layer on the first hole transport layer;
[0057] S3: mixing a piperazine carboxylic acid compound and an organic solvent in a preset ratio to form a passivation treatment solution, coating the passivation treatment solution on the surface of the first perovskite light absorbing layer, and performing annealing treatment to form a first interface passivation layer;
[0058] S4: forming a first electron transport layer on the first interface passivation layer;
[0059] S5: forming a first electrode layer on the first electron transport layer.
[0060] First, see Figure 2 , perform the step S1: provide a conductive substrate 111 , and form a first hole transport layer 112 on the conductive substrate 111 .
[0061] As an example, the conductive substrate 111 includes a rigid conductive substrate and a flexible conductive substrate.
[0062] As an example, the rigid conductive substrate includes any one of glass and a metal plate.
[0063] As an example, the flexible conductive substrate includes a transparent conductive film layer and a transparent conductive oxide film layer located above the transparent conductive film layer, wherein the material of the transparent conductive film layer includes at least one of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS) and polyimide (PI), and the material of the transparent conductive oxide film layer includes at least one of oxide films such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), indium-doped zinc oxide (IZO), and indium cerium oxide (ICO). In this embodiment, the conductive substrate 111 is preferably a PET / ITO flexible conductive substrate.
[0064] As an example, before forming the first hole transport layer 112 on the conductive substrate 111 , the method further includes a step of pre-treating the conductive substrate 111 .
[0065] As an example, pre-treating the conductive substrate 111 includes the following steps:
[0066] (1) The conductive substrate 111 is placed in acetone, ethanol and deionized water in turn for ultrasonic cleaning to remove oil-soluble impurities and water-soluble impurities on the conductive substrate 111.
[0067] (2) The conductive substrate 111 is subjected to UV-ozone treatment to further remove pollutants on the surface of the conductive substrate 111, and at the same time improve the surface properties of the conductive substrate 111, increase the surface energy and hydrophilicity of the conductive substrate 111, and promote the adhesion of subsequent film layers.
[0068] As an example, forming the first hole transport layer 112 on the conductive substrate 111 includes the following steps:
[0069] (1) preparing a first hole transport precursor solution, and coating the first hole transport precursor solution on the conductive substrate 111;
[0070] (2) Performing annealing treatment to form the first hole transport layer 112 .
[0071] As an example, the material of the first hole transport layer 112 includes but is not limited to at least one of nickel oxide, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz) and [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid (4PADCB).
[0072] As an example, the thickness of the first hole transport layer 112 is in the range of 5 to 30 nanometers.
[0073] Specifically, in this embodiment, the specific preparation method of the first hole transport precursor solution depends on the material composition of the first hole transport layer 112 to be formed. When the first hole transport layer 112 to be formed is composed of one material, such as when the first hole transport layer 112 to be formed is a nickel oxide layer, the first hole transport precursor solution can be formed by dissolving nickel oxide nanoparticles in deionized water or a suitable organic solvent; or, when the first hole transport layer 112 to be formed is a Me-4PACz layer, the first hole transport precursor solution can be formed by dissolving Me-4PACz powder in a suitable organic solvent (such as isopropanol, chloroform, etc.). When the first hole transport layer 112 to be formed is composed of two or more materials, the first hole transport precursor solution can be prepared by any of the following methods:
[0074] (a) Each material constituting the first hole transport layer 112 is prepared into a mixed solution, that is, the solutions or suspension solutions corresponding to each material constituting the first hole transport layer 112 are mixed together to form a composite first hole transport precursor solution.
[0075] (b) Each material constituting the first hole transport layer 112 is prepared into an independent solution, that is, each material constituting the first hole transport layer 112 corresponds to an independent solution, thereby forming the first hole transport precursor solution comprising multiple independent solutions. For such a first hole transport precursor solution comprising multiple independent solutions, in this embodiment, each of the independent solutions can be sequentially coated on the conductive substrate 111 by means of stacked coating, and after each of the independent solutions is coated, an intermediate annealing treatment can be selectively performed to promote the bonding between the layers and the curing of the materials. After the coating of the multiple independent solutions is completed, that is, after all the layers are coated, a final annealing treatment is performed to form the first hole transport layer 112 having a stacked arrangement including multiple material layers.
[0076] As an example, the coating method of coating the first hole transport precursor solution on the conductive substrate 111 includes at least one of spin coating, spray coating, printing, printing and scraping. In this embodiment, the first hole transport precursor solution is preferably coated on the conductive substrate 111 by spin coating. The spin coating time range is 10 to 40 seconds, and the spin coating speed range is 1000 to 5000 rpm.
[0077] As an example, the temperature range of the annealing treatment is 100-150° C., and the time range of the annealing treatment is 5-30 minutes.
[0078] Please see again Figure 2 , perform the step S2: forming a first perovskite light absorbing layer 113 on the first hole transport layer 112 .
[0079] As an example, forming the first perovskite light absorbing layer 113 includes the following steps:
[0080] (1) A first perovskite precursor solution of a certain concentration is prepared, the first perovskite precursor solution is coated on the first hole transport layer 112, and the first perovskite precursor solution is subjected to an anti-solvent treatment.
[0081] (2) Perform annealing treatment.
[0082] As an example, the general structural formula of the material of the first perovskite light absorbing layer 113 is ABX3, where A is MA + , FA + , Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ ,Ge 2+ Any one or a combination of at least two of the following, X is F - , Cl - ,I - Br - Any one or a combination of at least two of the following.
[0083] As an example, the thickness of the first perovskite light absorbing layer 113 is in the range of 300 to 800 nanometers.
[0084] As an example, the coating method of applying the first perovskite precursor solution on the first hole transport layer 112 includes any one of spraying, spin coating, drip coating, blade coating, roller coating, air knife coating and brush coating. In this embodiment, the first perovskite precursor solution is preferably coated on the first hole transport layer 112 by spin coating, wherein the spin coating can be completed in one step or in two steps, and the spin coating time range is 30 to 80 seconds, and the spin coating speed range is 2000 to 8000 rpm.
[0085] Specifically, in this embodiment, an anti-solvent is added dropwise when the spin coating time is 5 to 35 seconds, so as to perform anti-solvent treatment on the first perovskite precursor solution.
[0086] As an example, the anti-solvent includes any one of chlorobenzene, ethyl acetate, anisole, dimethyl ethyl carbonate, ethanol and diethyl ether.
[0087] As an example, the temperature range of the annealing treatment is 100-150° C., and the time range of the annealing treatment is 10-60 minutes.
[0088] In a specific example, forming the first perovskite light absorbing layer 113 includes the following steps: (1) dissolving methyl ammonium chloride (MACl), lead iodide (PbI2), cesium iodide (CsI) and methyl ammine iodide (FAI) in a mixed solvent consisting of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) in a volume ratio of 1:4, and stirring for 8 hours until the mixture is uniform, so as to form a FA solution with a concentration of 1.6 mol / mL; 0.95 Cs 0.05 PbI3 first perovskite precursor solution. (2) The FA 0.95 Cs 0.05 The PbI3 first perovskite precursor solution was spin-coated on the surface of the first hole transport layer 112. The spin-coating speed was 4000 rpm, the spin-coating time was 40 s, and at the 33rd second of the spin-coating, 200 μL of chlorobenzene was added dropwise for anti-solvent treatment. (3) Annealing was performed at a temperature of 100° C. for 60 minutes to form the first perovskite light absorbing layer 113.
[0089] In another specific example, forming the first perovskite light absorbing layer 113 includes the following steps: (1) dissolving methyl bromide (FABr), PbI2, CsI, FAI, cesium bromide (CsBr) and lead bromide (PbBr2) in a mixed solvent consisting of DMSO and DMF in a volume ratio of 1:4, and stirring at a temperature of 50° C. for 2 hours until the mixture is uniform, so as to form a FABr with a concentration in the range of 1.15 mol / mL; 0.8 Cs 0.2 PbI 1.95 Br 1.05 The first perovskite precursor solution. (2) The FA is mixed in two steps. 0.8 Cs 0.2 PbI 1.95 Br 1.05 The first perovskite precursor solution is spin-coated on the surface of the first hole transport layer 112. The first step is spin-coated at a rotation speed of 2000 rpm for 10 seconds, and the second step is spin-coated at a rotation speed of 6000 rpm for 40 seconds. 20 seconds before the end of the spin coating, chlorobenzene is added dropwise for anti-solvent treatment. (3) Annealing is performed at a temperature of 100° C. for 10 minutes to form the first perovskite light absorbing layer 113.
[0090] It should be noted that the specific composition of the first perovskite light absorbing layer 113 can be adjusted and optimized according to the actual application requirements to meet specific photoelectric performance requirements. For example: to improve the efficiency of the battery, a perovskite material with a wider bandgap can be selected, and a perovskite material containing tin can also be selected to improve stability. Therefore, the preparation of the first perovskite precursor solution and the material composition of the first perovskite light absorbing layer 113 formed subsequently are not fixed, but can be adjusted according to the actual application requirements, and are not limited to the above two examples.
[0091] Please see again Figure 2 , perform step S3: mix the piperazine carboxylic acid compound and the organic solvent in a preset ratio to form a passivation treatment solution, apply the passivation treatment solution on the surface of the first perovskite light absorbing layer 113, and perform annealing treatment to form a first interface passivation layer 114.
[0092] Specifically, the passivation treatment solution is prepared by mixing the piperazine carboxylic acid compound and the organic solvent in a preset ratio. The specific mixing ratio depends on the concentrations of the piperazine carboxylic acid compound and the organic solvent, and is not limited here.
[0093] As an example, the piperazine carboxylic acid compound includes but is not limited to at least one of piperazine-DL-malate, 2-piperazine acetic acid and 4-piperazine benzoic acid. In this embodiment, the piperazine carboxylic acid compound is preferably piperazine-DL-malate.
[0094] As an example, the organic solvent includes at least one of isopropanol, methanol, ethanol and ethyl acetate. In this embodiment, the organic solvent is preferably isopropanol.
[0095] Specifically, in this embodiment, the piperazine-DL-malate solid powder is added to the isopropanol solution, and the piperazine-DL-malate solid powder is evenly distributed in the isopropanol solution by continuous shaking and stirring, thereby preparing the desired passivation treatment solution.
[0096] As an example, the concentration range of the piperazine carboxylic acid compound in the passivation treatment solution is 0.1 to 2 mg / mL.
[0097] As an example, the coating method of applying the passivation treatment liquid to the surface of the first perovskite light absorbing layer 113 includes any one of spraying, spin coating, drip coating, blade coating, roller coating, air knife coating and brush coating. In this embodiment, the passivation treatment liquid is preferably coated on the surface of the first perovskite light absorbing layer 113 by spin coating. The spin coating time range is 10 to 60 seconds, and the spin coating speed range is 1000 to 6000 rpm.
[0098] As an example, the temperature range of the annealing treatment performed after the passivation treatment solution is applied to the surface of the first perovskite light absorbing layer 113 is 100 to 150° C., and the time range of the annealing treatment is 5 to 30 seconds.
[0099] As an example, the thickness of the first interface passivation layer 114 is in the range of 1 to 15 nanometers.
[0100] Specifically, the first interface passivation layer 114 of this embodiment includes a piperazine group and a carboxylic acid group, wherein the nitrogen atom in the piperazine group and the oxygen atom in the carboxylic acid group can react with the metal cations (such as Pb 2+ The coordination effect can effectively passivate the defects on the surface and grain boundaries of the first perovskite light absorbing layer 113, reduce the uncoordinated sites of metal cations on the surface of the first perovskite light absorbing layer 113, thereby effectively inhibiting non-radiative recombination and improving charge transfer efficiency.
[0101] Furthermore, the carboxylic acid groups in the first interface passivation layer 114 of this embodiment have a multi-point passivation effect. On the one hand, the hydroxyl groups in the carboxylic acid groups can form hydrogen bonds or weak electrostatic interactions with the iodine ions on the surface of the first perovskite light absorption layer 113, thereby enhancing the adhesion of the first interface passivation layer 114 to the surface of the first perovskite light absorption layer 113 and significantly reducing the defect state density on the surface of the first perovskite light absorption layer 113. On the other hand, the protons (H + ) can be transferred to the alkaline sites on the surface of the first perovskite light-absorbing layer 113 to form carboxylate ions (-COO - ), the carboxylate ions can combine with the metal cations on the surface of the first perovskite light absorbing layer 113 through electrostatic interaction, further enhancing the interface passivation effect, reducing non-radiative recombination, and effectively improving the stability of the first perovskite light absorbing layer 113.
[0102] Please see again Figure 2 , perform the step S4: forming a first electron transport layer 115 on the first interface passivation layer 114 .
[0103] As an example, the first electron transport layer 115 is formed by any one of thermal evaporation, sputtering, spraying, blade coating and spin coating.
[0104] As an example, the material of the first electron transport layer 115 includes fullerene (C 60 ), at least one of a fullerene derivative (PCBM) and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP).
[0105] As an example, the thickness of the electron transport layer is in the range of 5 to 50 nanometers.
[0106] Please see again Figure 2 , perform the step S5: forming a first electrode layer 117 on the first electron transport layer 115 .
[0107] As an example, a first buffer layer 116 is further formed between the first electron transport layer 115 and the first electrode layer 117 .
[0108] As an example, the first buffer layer 116 is formed by any one of atomic layer deposition, thermal evaporation, sputtering, doctor blading, spin coating and spray coating.
[0109] As an example, the thickness of the first buffer layer 116 is in the range of 5 to 100 nanometers.
[0110] As an example, the material of the first buffer layer 116 includes SnO x , where the value range of X is 1 to 2.
[0111] As an example, the first electrode layer 117 is formed by thermal evaporation, magnetron sputtering, chemical vapor deposition, atomic layer deposition or other suitable methods.
[0112] As an example, the material of the first electrode layer 117 includes any one of copper, silver, aluminum, nickel, gold and ITO.
[0113] At this point, a perovskite battery has been produced.
[0114] In the preparation method of a perovskite battery provided in this embodiment, by introducing a first interface passivation layer 114 including a piperazine group and a carboxylic acid group into the first perovskite light absorption layer 113 and the first electron transport layer 115, multiple optimizations of the first perovskite light absorption layer 113 are achieved. The first interface passivation layer 114 not only effectively fills the grain boundary voids of the first perovskite light absorption layer 113, inhibits excessive crystal growth at the grain boundary, but also significantly reduces the roughness of the first perovskite surface. In addition, the first interface passivation layer 114 also effectively passivates the surface and grain boundary defects of the first perovskite light absorption layer 113, reduces the effect of these defects on the charge transfer efficiency, thereby effectively inhibiting the occurrence of non-radiative recombination processes. In addition, the first interface passivation layer 114 also effectively regulates the energy level alignment between the first perovskite light absorption layer 113 and the first electron transport layer 115, reduces charge accumulation, enhances charge transfer capability, and prolongs carrier lifetime, thereby significantly improving the overall performance of the perovskite battery.
[0115] The preparation method of the perovskite battery of the present invention is further introduced below in combination with a specific example and a comparative example.
[0116] In a specific example, the method for preparing the perovskite battery includes the following steps:
[0117] (1) First, a PET / ITO flexible conductive substrate with a length of 15 cm and a width of 15 cm was selected, and the PET / ITO flexible conductive substrate was placed in acetone, ethanol and deionized water for ultrasonic cleaning in turn, and each was cleaned for 20 minutes, and then wiped clean. Thereafter, the PET / ITO flexible conductive substrate was subjected to UV-ozone treatment for 20 minutes to further clean and activate the surface of the PET / ITO flexible conductive substrate.
[0118] (2) Prepare a first hole transport precursor solution, which includes a first solution and a second solution. The first solution is obtained by dissolving nickel oxide nanoparticles in deionized water and performing ultrasonic treatment for 10 minutes, and its concentration is 10 mg / mL; the second solution is obtained by dissolving Me-4PACz in an isopropanol solution, and its concentration is 0.5 mg / mL. In this example, in the process of forming the first hole transport layer 112, the following steps are included: first, the first solution is spin-coated on the surface of the PET / ITO flexible conductive substrate at a speed of 2000 rpm, and the spin coating duration is 20s. Subsequently, annealing treatment is performed at a temperature of 100°C for 10 minutes to form a nickel oxide hole transport layer. Next, the second solution is spin-coated: the second solution is spin-coated on the formed nickel oxide hole transport layer at a speed of 3000 rpm, and the spin coating time is 30s. Afterwards, an annealing treatment is also performed at a temperature of 100° C. for 10 minutes to form a Me-4PACz hole transport layer. Finally, the nickel oxide hole transport layer and the Me-4PACz hole transport layer together constitute the first hole transport layer 112 .
[0119] (3) MACl, PbI2, CsI and FAI were dissolved in a mixed solvent consisting of DMSO and DMF in a volume ratio of 1:4 and stirred for 8 hours until the mixture was uniform to form a FA solution with a concentration of 1.6 mol / mL. 0.95 Cs 0.05 The first perovskite precursor solution of PbI3 was prepared. Then, the FA was coated by a one-step spin coating method. 0.95 Cs 0.05The PbI3 first perovskite precursor solution was spin-coated on the surface of the first hole transport layer 112 at a speed of 4000 rpm for 40 seconds, and at 33 seconds of spin coating, 200 μL of chlorobenzene was added for anti-solvent treatment. Finally, an annealing treatment was performed at a temperature of 100° C. for 60 minutes to form the first perovskite light absorbing layer 113.
[0120] (4) Add piperazine-DL-malate to the isopropanol solution and shake and stir until the mixture is uniformly mixed to form a piperazine-DL-malate passivation treatment solution with a concentration of 0.2 mg / mL. Then, the piperazine-DL-malate passivation treatment solution is spin-coated on the surface of the first perovskite light absorbing layer 113 at a speed of 3000 rpm for 30 seconds. Thereafter, annealing is performed at a temperature of 100° C. for 10 minutes to form the first interface passivation layer 114. Figure 3 As shown, it is a scanning electron microscope (SEM) image presented after the first interface passivation layer 114 is formed on the surface of the first perovskite light absorbing layer 113 in this example. The grain size distribution of the first perovskite light absorbing layer 113 is uniform and consistent, and the grains are closely arranged to form a highly ordered crystalline morphology, which indicates that the first interface passivation layer 114 helps to promote the uniform growth and crystallization of the grains. In addition, the introduction of the first interface passivation layer 114 significantly reduces the grain boundary voids, making the grain boundaries of the first perovskite light absorbing layer 113 almost invisible, presenting a continuous and complete microstructure. This perovskite structure without grain boundary voids helps to reduce the recombination rate of carriers and improve the charge transfer efficiency.
[0121] (5) Using thermal evaporation method to prepare C on the first interface passivation layer 114 60 A thin film is formed to form the first electron transport layer 115. Then, SnO2 is deposited on the first electron transport layer 115 by atomic layer deposition to form the first buffer layer 116. Finally, a silver layer is deposited on the first buffer layer 116 by thermal evaporation as the first electrode layer 117 to prepare the perovskite battery, and the perovskite battery is a flexible perovskite battery. Figure 4 As shown, the power conversion efficiency (PCE) of the flexible perovskite battery formed is 21.13%, and the open circuit voltage (V OC ) is 1.10V, short-circuit current (J SC ) is 24.75 mA / cm 2 , the fill factor (FF) is 77.53%. In this example, the flexible perovskite battery formed has the characteristics of being light, bendable and thin, and can also be integrated on clothing or even curved electronic devices, and has broad application prospects.
[0122] The preparation method of the perovskite battery in the comparative example is basically the same as the preparation method of the perovskite battery in a specific example of the present invention, except that the first interface passivation layer 114 is not introduced between the first perovskite light absorbing layer 113 and the first electron transport layer 115. Figure 5 As shown in FIG. 1 , it is a scanning electron microscope image presented when the first interface passivation layer 114 is not formed on the surface of the first perovskite light absorption layer 113 in the comparative example. It can be seen that the surface of the first perovskite light absorption layer 113 is relatively rough, and the grain size distribution is uneven, in which larger grains coexist with smaller grains, resulting in poor overall crystallinity. In addition, there are obvious grain boundary voids on the surface of the first perovskite light absorption layer 113, and these voids may become charge recombination centers, reducing the photoelectric conversion efficiency of the perovskite battery. Figure 6 As shown, it is a current density and voltage characteristic curve of the perovskite battery formed in the comparative example, wherein the PCE of the perovskite battery is 19.83%, V OC is 1.07V, J SC 24.25mA / cm 2 , FF is 75.98%. The performance of the perovskite battery formed in the comparative example is significantly lower than that of the perovskite battery formed in a specific example of the present invention. Figure 7 As shown, the power conversion efficiency of the perovskite cell formed in a specific example of the present invention is significantly higher than the power conversion efficiency of the perovskite cell formed in the comparative example.
[0123] Embodiment 2
[0124] This embodiment provides a method for preparing a perovskite battery. The method for preparing a perovskite battery in this embodiment is basically the same as the method for preparing a perovskite battery in Example 1, except that it also includes a step of forming a bottom battery structure layer, and the bottom battery structure layer is formed on the surface of the first electrode layer 117.
[0125] As an example, the formation of the bottom battery structure layer includes the following steps:
[0126] (1) forming a second hole transport layer 121 on the first electrode layer 117;
[0127] (2) forming a second perovskite light absorption layer 122 on the second hole transport layer 121, wherein the bandgap width of the material of the second perovskite light absorption layer 122 is smaller than the bandgap width of the material of the first perovskite light absorption layer 113;
[0128] (3) forming a second interface passivation layer 123 on the second perovskite light absorbing layer 122;
[0129] (4) forming a second electron transport layer 124 on the second interface passivation layer 123;
[0130] (5) Forming a second electrode layer 126 on the second electron transport layer 124 .
[0131] As an example, the material of the second hole transport layer 121 includes but is not limited to at least one of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), nickel oxide (NiO), cuprous thiocyanate (CuSCN) and poly(3-hexylthiophene) (P3HT).
[0132] As an example, forming the second hole transport layer 121 includes the following steps:
[0133] (1) preparing a second hole transport precursor solution, and coating the second hole transport precursor solution on the first electrode layer 117 .
[0134] (2) Performing annealing treatment to form the second hole transport layer 121 .
[0135] Specifically, in this embodiment, the specific preparation method of the second hole transport precursor solution depends on the material composition of the second hole transport layer 121 to be formed. When the second hole transport layer 121 to be formed is composed of one material, such as when the second hole transport layer 121 to be formed is a PEDOT:PSS layer, the second hole transport precursor solution can be directly formed using a PEDOT:PSS aqueous suspension solution. Alternatively, if the second hole transport layer 121 to be formed is a nickel oxide layer, the second hole transport precursor solution can be formed by dissolving nickel oxide nanoparticles in deionized water or a suitable organic solvent. When the second hole transport layer 121 to be formed is composed of two or more materials, the second hole transport precursor solution can be prepared in any of the following ways:
[0136] (a) Each material constituting the second hole transport layer 121 is prepared into a mixed solution, that is, the solutions or suspensions corresponding to each material constituting the second hole transport layer 121 are mixed together to form a composite second hole transport precursor solution.
[0137] (b) Each material constituting the second hole transport layer 121 is prepared into an independent solution, that is, each material constituting the second hole transport layer 121 corresponds to an independent solution, thereby forming the second hole transport precursor solution comprising multiple independent solutions. For such a second hole transport precursor solution comprising multiple independent solutions, in this embodiment, each of the independent solutions can be sequentially coated on the first electrode layer 117 by means of stacked coating, and after each of the independent solutions is coated, an intermediate annealing treatment can be selectively performed to promote the bonding between the layers and the curing of the materials. After the coating of the multiple independent solutions is completed, that is, after all the layers are coated, a final annealing treatment is performed to form a stacked arrangement of the second hole transport layer 121 comprising multiple material layers.
[0138] As an example, the coating method of coating the second hole transport precursor solution on the first electrode layer 117 includes any one of spray coating, spin coating, drop coating, blade coating, roller coating and air knife coating. In this embodiment, the second hole transport precursor solution is preferably coated on the first electrode layer 117 by spin coating.
[0139] As an example, the temperature range of the annealing treatment is 50-150° C., and the time range of the annealing treatment is 5-15 minutes.
[0140] In a specific example, the process of forming the second hole transport layer 121 includes: preparing a PEDOT:PSS solution, and spin coating the PEDOT:PSS solution on the first electrode layer 117 at a rotation speed of 4000 rpm for 30 seconds. Subsequently, annealing treatment is performed in an air environment at 100° C. for 10 minutes to form the second hole transport layer 121.
[0141] As an example, forming the second perovskite light absorbing layer 122 includes the following steps:
[0142] (1) preparing a second perovskite precursor solution of a certain concentration, coating the second perovskite precursor solution on the second hole transport layer 121, and performing an anti-solvent treatment on the second perovskite precursor solution.
[0143] (2) Perform annealing treatment.
[0144] As an example, the structural formula of the material of the second perovskite light absorbing layer 122 is ABX3, where A is MA + , FA + , Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ ,Ge2+ Any one or a combination of at least two of the following, X is F - , Cl - ,I - Br - Any one or a combination of at least two of the following.
[0145] As an example, the concentration range of the second perovskite precursor solution is 1 to 3 mol / mL.
[0146] As an example, the coating method of coating the second perovskite precursor solution on the second hole transport layer 121 includes any one of spraying, spin coating, drip coating, blade coating, roller coating, air knife coating and brush coating. In this embodiment, the second perovskite precursor solution is preferably coated on the second hole transport layer 121 by spin coating, and the spin coating is completed in two steps, wherein the first step of spin coating has a time range of 5 to 15 s, the first step of spin coating has a speed range of 500 to 1500 rpm, the second step of spin coating has a time range of 20 to 60 s, and the second step of spin coating has a speed range of 3000 to 5000 rpm.
[0147] Specifically, in this embodiment, an anti-solvent is added dropwise when the spin coating time is 5 to 15 seconds remaining to perform anti-solvent treatment on the second perovskite precursor solution. The anti-solvent used in the anti-solvent treatment on the second perovskite precursor solution is the same as the anti-solvent used in the anti-solvent treatment on the first perovskite precursor solution.
[0148] As an example, the temperature range of the annealing treatment performed after the anti-solvent treatment of the second perovskite precursor solution is 50 to 150° C., and the time range of the annealing treatment is 5 to 10 minutes.
[0149] In a specific example, forming the second perovskite light absorbing layer 122 includes the following steps: (1) dissolving lead iodide (PbI2), methyl ammonium iodide (MAI), FAI and stannous iodide (SnI2) in a mixed solvent consisting of DMSO and DMF in a volume ratio of 1:2, and stirring at room temperature for 2 hours until the mixture is uniform, so as to form a FA solution with a concentration of 1.8 mol / mL. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I3 second perovskite precursor solution. (2) The FA is prepared by a two-step method. 0.7 MA 0.3 Pb 0.5 Sn 0.5I3 The second perovskite precursor solution is spin-coated on the surface of the second hole transport layer 121. The first step is spin-coated at a rotation speed of 1000 rpm for 10 seconds, and the second step is spin-coated at a rotation speed of 4000 rpm for 40 seconds. At 10 seconds before the end of the spin coating, chlorobenzene is added dropwise for anti-solvent treatment. (3) Annealing is performed at a temperature of 100° C. for 10 minutes to form the second perovskite light absorbing layer 122.
[0150] As an example, the process of forming the second interface passivation layer 123 includes: preparing a passivation solution, coating the passivation solution on the second perovskite light absorbing layer 122, and performing annealing to form the second interface passivation layer 123, wherein the composition of the passivation solution used to form the second interface passivation layer 123 is the same as or different from the composition of the passivation treatment solution used to form the first interface passivation layer 114.
[0151] Specifically, when the composition of the passivation solution used to form the second interface passivation layer 123 is the same as the composition of the passivation treatment solution used to form the first interface passivation layer 114, that is, the passivation solution is a mixture of the piperazine carboxylic acid compound and the organic solvent in a specific proportion, the material of the formed second interface passivation layer 123 includes at least one of piperazine-DL-malate, 2-piperazineacetic acid and 4-piperazinebenzoic acid.
[0152] Specifically, when the composition of the passivation solution used to form the second interface passivation layer 123 is different from the composition of the passivation treatment solution used to form the first interface passivation layer 114, the material of the formed second interface passivation layer 123 includes at least one of ethylenediamine dihydroiodide (EDAI), 1,3-diaminopropane dihydroiodide (PDADI), 4-methoxyphenethylammonium iodide (PEAI), phenethylammonium bromide (PEABr) and 4-trifluoromethylphenethylammonium chloride (CF3-PEACl), wherein the specific composition of the passivation solution is selected according to the actual thickness of the second interface passivation layer 123 to be formed, the passivation effect, etc.
[0153] As an example, the coating method of coating the passivation solution on the second perovskite light absorbing layer 122 includes any one of spraying, spin coating, drip coating, blade coating, roller coating, air knife coating and brush coating.
[0154] As an example, the temperature range of the annealing treatment performed after the passivation solution is coated on the second perovskite light absorbing layer 122 is 50-150° C.
[0155] In a specific example, the process of forming the second interface passivation layer 123 includes: adding piperazine-DL-malate to an isopropanol solution, and shaking and stirring until the mixture is uniform, so as to form a piperazine-DL-malate passivation solution with a concentration of 0.2 mg / mL. Then, the piperazine-DL-malate passivation solution is spin-coated on the surface of the second perovskite light absorbing layer 122 at a speed of 3000 rpm, and the spin-coating time is 30 seconds. Thereafter, annealing treatment is performed at a temperature of 100° C., and the annealing treatment time is 10 minutes to form the second interface passivation layer 123.
[0156] In another specific example, the process of forming the second interface passivation layer 123 includes: adding EDAI to an isopropanol solution and stirring until the mixture is uniform to form an EDAI passivation solution with a concentration of 0.5 mg / mL, and spin-coating the EDAI passivation solution on the second perovskite light absorbing layer 122 at a speed of 4000 rpm for 30 seconds. Subsequently, an annealing treatment is performed at a temperature of 100° C. for 10 minutes to form the second interface passivation layer 123.
[0157] Of course, in other examples, the second interface passivation layer 123 may also be prepared from the passivation solution containing other material components, which is not specifically limited here.
[0158] As an example, the second electron transport layer 124 is formed by thermal evaporation, atomic layer deposition, spin coating, doctor blade coating, slit deposition, spray coating, chemical bath deposition or other suitable methods.
[0159] As an example, the material of the second electron transport layer 124 includes PCBM, C 60 , any one of tin dioxide, titanium oxide and zinc oxide.
[0160] In a specific example, a 25 mg / ml PCBM solution is spin-coated on the second interface passivation layer 123 at a rotation speed of 2000 rpm for 30 seconds to form the second electron transport layer 124 .
[0161] As an example, a second buffer layer 125 is further formed between the second electron transport layer 124 and the second electrode layer 126 .
[0162] As an example, the second buffer layer 125 is formed by any one of scraping, spin coating, spraying, atomic layer deposition, thermal evaporation and sputtering. In this embodiment, the second buffer layer 125 is preferably formed by spin coating. The spin coating time range is 10 to 50 seconds, and the spin coating speed range is 2000 to 6000 rpm.
[0163] As an example, the material of the second buffer layer 125 includes at least one of BCP, lithium fluoride (LiF) and cesium carbonate (Cs 2 CO 3 ).
[0164] In a specific example, a supersaturated BCP solution is spin-coated on the second electron transport layer 124 at a rotation speed of 4000 rpm for 30 seconds, and annealed at a temperature of 100° C. for 1 minute to form the second buffer layer 125 .
[0165] As an example, the second electrode layer 126 is formed by thermal evaporation, magnetron sputtering, chemical vapor deposition, atomic layer deposition or other suitable methods.
[0166] As an example, the material of the second electrode layer 126 includes any one of copper, silver, aluminum, nickel, gold and ITO.
[0167] In a specific example, a silver layer is deposited on the second buffer layer 125 by thermal evaporation to form the second electrode layer 126 .
[0168] At this point, a perovskite battery structure is produced, such as Figure 8 shown.
[0169] In a method for preparing a perovskite battery in this embodiment, an underlying battery structure layer is formed on the surface of the first electrode layer 117, thereby achieving optimized superposition of perovskite layers with different band gaps, effectively expanding the spectral absorption range of the perovskite battery, and forming an efficient stacked perovskite battery structure. In the stacked perovskite battery structure, in addition to introducing a first interface passivation layer 114 including piperazine groups and carboxylic acid groups in the first perovskite light absorption layer 113 and the first electron transport layer 115 to achieve multiple optimizations of the first perovskite light absorption layer 113, a second interface passivation layer 123 is also introduced between the second perovskite light absorption layer 122 and the second electron transport layer 124 in the bottom battery structure layer, and the second interface passivation layer 123 can also be formed of a material including piperazine groups and carboxylic acid groups to further remove surface and grain boundary defects of the second perovskite light absorption layer 122, inhibit non-radiative recombination, and at the same time regulate the energy level alignment between the second perovskite light absorption layer 122 and the first electron transport layer 115, reduce charge accumulation, enhance charge transport capability, and extend carrier lifetime, thereby improving the overall performance of the stacked perovskite battery structure. It should be noted that Figure 8 The structural order in the figure is for schematic display only and should be inverted in actual application, that is, the bottom battery structure layer should be located at the bottom.
[0170] Embodiment 3
[0171] The present embodiment provides a perovskite cell structure, the perovskite cell structure comprising a conductive substrate 111, a first hole transport layer 112, a first perovskite light absorption layer 113, a first interface passivation layer 114, a first electron transport layer 115 and a first electrode layer 117 stacked in sequence, wherein the perovskite cell structure is obtained by using any one of the perovskite cell preparation methods in Embodiment 1 and Embodiment 2. The perovskite cell structure of the present embodiment achieves multiple optimizations of the first perovskite light absorption layer 113 by introducing a first interface passivation layer 114 including a piperazine group and a carboxylic acid group between the first perovskite light absorption layer 113 and the first electron transport layer 115. The first interface passivation layer 114 not only effectively passivates the defects on the surface and grain boundaries of the first perovskite light absorption layer 113, inhibiting the occurrence of non-radiative recombination processes, but also effectively regulates the energy level alignment between the first perovskite light absorption layer 113 and the first electron transport layer 115, thereby enhancing the charge transfer capability and extending the carrier lifetime, thereby significantly improving the overall performance of the perovskite battery.
[0172] In summary, the present invention provides a method and structure for preparing a perovskite cell, which significantly improves the performance of the perovskite cell by introducing a specific interface passivation layer between the first perovskite light-absorbing layer and the first electron transport layer. The introduction of the interface passivation layer effectively passivates the defects on the surface of the first perovskite light-absorbing layer and at its grain boundaries, and reduces the interface defect state density between the first perovskite light-absorbing layer and the first electron transport layer, thereby effectively suppressing the occurrence of non-radiative recombination processes. In addition, the interface passivation layer also optimizes the energy band structure of the first perovskite light-absorbing layer, significantly improves the extraction efficiency of carriers, and thus greatly improves the overall performance of the perovskite solar cell. The preparation method of the present invention is simple and efficient, can significantly improve the overall performance of the perovskite cell, and can be widely used in photovoltaic power generation, photoelectric detection and other fields. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.
[0173] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a perovskite battery, characterized in that: The following steps are involved: Providing a conductive substrate, and forming a first hole transport layer on the conductive substrate; forming a first perovskite light absorbing layer on the first hole transport layer; Mixing a piperazine carboxylic acid compound and an organic solvent in a preset ratio to form a passivation treatment solution, coating the passivation treatment solution on the surface of the first perovskite light absorbing layer, and performing an annealing treatment to form a first interface passivation layer; forming a first electron transport layer on the first interface passivation layer; A first electrode layer is formed on the first electron transport layer.
2. The method for preparing a perovskite battery according to claim 1, characterized in that: The piperazine carboxylic acid compound includes at least one of piperazine-DL-malate, 2-piperazineacetic acid and 4-piperazinebenzoic acid.
3. The method for preparing a perovskite battery according to claim 1, characterized in that: The concentration range of the piperazine carboxylic acid compound in the passivation treatment solution is 0.1-2 mg / mL.
4. The method for preparing a perovskite battery according to claim 1, characterized in that: The thickness of the first interface passivation layer is in the range of 1 to 15 nanometers.
5. The method for preparing a perovskite battery according to claim 1, characterized in that: The organic solvent includes at least one of isopropanol, methanol, ethanol and ethyl acetate.
6. The method for preparing a perovskite battery according to claim 1, characterized in that: The general structural formula of the material of the first perovskite light absorbing layer is ABX3, wherein A is MA + , FA + , Cs + Any one or a combination of at least two of the following, B is Pb 2+ Sn 2+ ,Ge 2+ Any one or a combination of at least two of the following, X is F - , Cl - ,I - Br - Any one or a combination of at least two of the following.
7. The method for preparing a perovskite battery according to claim 1, characterized in that: The method further includes the step of forming a bottom battery structure layer, wherein the bottom battery structure layer is formed on the surface of the first electrode layer.
8. The method for preparing a perovskite battery according to claim 7, characterized in that: The formation of the bottom battery structure layer comprises the following steps: forming a second hole transport layer on the first electrode layer; forming a second perovskite light absorption layer on the second hole transport layer, wherein the bandgap width of the material of the second perovskite light absorption layer is smaller than the bandgap width of the material of the first perovskite light absorption layer; forming a second interface passivation layer on the second perovskite light absorbing layer; forming a second electron transport layer on the second interface passivation layer; A second electrode layer is formed on the second electron transport layer.
9. The method for preparing a perovskite battery according to claim 8, characterized in that: The process of forming the second interface passivation layer includes: preparing a passivation solution, coating the passivation solution on the second perovskite light absorbing layer, and performing annealing to form the second interface passivation layer, wherein the composition of the passivation solution used to form the second interface passivation layer is the same as or different from the composition of the passivation treatment solution used to form the first interface passivation layer.
10. A perovskite battery structure, characterized in that: The perovskite cell structure comprises a conductive substrate, a first hole transport layer, a first perovskite light absorption layer, a first interface passivation layer, a first electron transport layer and a first electrode layer stacked in sequence, wherein the perovskite cell structure is obtained by the preparation method of the perovskite cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Perovskite cell, photovoltaic module, photovoltaic power generation system and electric equipment
CN115955848A
Perovskite solar cell
CN117998948A
Perovskite solar cell based on 1-(2-methoxyphenyl) piperazine salt passivation
CN118785731A
Cited By
Organic-inorganic hybrid perovskite solar cell and preparation method thereof
CN122497199A